Magnitude of Snake Bite and Drowing During Monsoon Flood in Two Districts of Bangladesh - Reza, AM Selim; Islam, SM Nurul; Ghosh, Anirudha; Rahman, Md Ridwanur; Faiz, MA; Rahim, Abdur (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Snake bite and drowning is very common during the season of monsoon flood. Objective: The purpose of the present study was to see the magnitude of snake bite and drowning during monsoon flood season in two districts of Bangladesh. Methodology: This cross sectional study was conducted from May 2012 to October 2012 in the most commonly flood affected districts of Bangladesh which were Shirajgonj and Pabna. All the people living in these two districts were selected as study population. Data regarding snake bite and drowning were collected from existing health facilities at Upazila Health Complexes, district hospital, private hospitals, print media like local and national newspapers, Medical College Hospitals and police station. Result: A total number of 9 Upazila in Sirajgonj District and another 9 upazila in Pabna district were included in this study. In Sirajgonj district drowning reported were in 140 cases and snake bite was in 49 cases. Furthermore, among 49 cases of snake bite death was occurred in 7(14.3%) cases in Sirajgonj District. Interestingly Shahzadpur, Shirajgonj sadar and Ullapara were the most common reported Upazila for drowning cases which were 38(27.1%) cases, 21(15.0%) cases and 20(l4.3%) cases respectively. However, among these high prone drowning area, snake bite is reported less commonly and Kazipur was the highest reported area for snake bite which was 25(51.0%) cases. On the other hand, Pabna district drowning reported cases were in 58 and snake bite was in 62 cases. Furthermore, among 62 cases of snake bite death was occurred in 17(27.4%) cases. Sujanagar, Bera and Faridpur were the most common reported area for drowning which were 11, 10 and 9 cases respectively. However, Chatmohar was the most commonly reported by snake bite which was 20(32.3%) cases. Conclusion: Drowning is more commonly occurred in Sirajgonj district than Pabna. However, Pabna district is found a snake bite prone area. J Shaheed Suhrawardy Med Coll, 2015; 7(1):3-5